ASYMMETRY PROCESSES OF SOCIO-ECONOMIC DEVELOPMENT OF THE NATIONAL ECONOMY AND ITS REGULATION - Родченко, В. Б. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The article is devoted phenomenon of asymmetry of social and economic development. Reviewed the contents of the category. The results of the rated of asymmetry on the example of trade in goods and services in urban complexes of Ukraine. Proposed conceptual approach to the regulation of the asymmetry of urban development.